2007
DOI: 10.1584/jpestics.g06-19
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of the disposition of the molluscicidal saponin deltonin from Balanites aegyptiaca in a snail species (Biomphalaria glabrata) and in mice

Abstract: A mixture of deltonin and 25-isodeltonin (approx. 1 : 1) was found to be the molluscicidal principle in seeds of Balanites aegyptiaca (L.) Del. The disposition in the schistosomiasis vector Biomphalaria glabrata and in mice was studied. Snails were exposed to 3 H-labelled saponin in water. Administration to mice was oral (O) and intravenous (IV). Snails absorbed the compounds rapidly and showed a high degree of bioaccumulation. The highest concentration was found in the foot followed by the intestines. Snails … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The varying potencies of each plant part may be due to the differences in concentration and/or the type of the active ingredient(s) present in each part [22] . In this observation, water extracts of seeds and mesocarps were more potent than the water extract of endocarps, perhaps due to the more concentrations of saponins in the mesocarps and seeds, and also presence of high amount of deltonin in the seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The varying potencies of each plant part may be due to the differences in concentration and/or the type of the active ingredient(s) present in each part [22] . In this observation, water extracts of seeds and mesocarps were more potent than the water extract of endocarps, perhaps due to the more concentrations of saponins in the mesocarps and seeds, and also presence of high amount of deltonin in the seeds.…”
Section: Discussionmentioning
confidence: 99%
“…These glucosides are responsible for the antidiabtic and antimicrobial properties of the tree extract (Varshncy & Vyas (1982); Saeed et al, 1995;Kapseu et al, 1997;Ansari et al 2006;Breimer et al, 2007).…”
Section: Glucosidesmentioning
confidence: 99%
“…In addition to the above phytochemicals, presence of 1-10-methyln-heptacosane (Ansari et al, 2006), balanitol (Cordano et al, 1978), bergapten (Seida et al, 1981;Breimer et al, 2007), cryptogenin, deltoin (Speroni et al, 2005), furanocoumarin (Khare 2007) and marmesin (Ansari et al 2006;Breimer et al, 2007) has been reported from the bark of B. aegyptiaca. Presence of Protodeltoin (Speroni et al, 2005) and 6-phenyl-2(H)-1,2,4-triazin-5-one oxime (Kusch et al, 2011) has been reported from the seed of B. aegyptiaca.…”
Section: Other Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins are traditionally extracted into water/ethanol mixtures, after which the ethanol is removed by evaporation and the saponins extracted from the water phase into 1-butanol (27,28). During the last decade there have been considerable efforts to improve this methodology, mainly on the extraction of ginseng saponins and glycyrrhizic acid, and also escin from horse chestnut.…”
Section: Extractionsmentioning
confidence: 99%